THE INFLUENCE OF BRAND AWARENESS, BRAND IMAGE, PERCEIVED QUALITY AND BRAND LOYALTY ON BRAND EQUITY IN BANKING SECTOR - Suyono Saputra (Management Department, Faculty of Economics and Business, Universitas Jambi, 2022)
The purpose of this study was to examine the effect of brand awareness, brand image, perceived quality, and loyalty to brand equity in the banking sector. The samples in this study were 240 respondents who registered as customers of 40 banking branch offices. The results of statistical tests using SEM-PLS show that there are only brand loyalty and brand awareness that have a significant effect on brand equity in banking sectors. While brand image and perceived quality have no significant effect, there is also no positive significance of brand image as a mediation to the relationship between brand awareness and brand equity. These findings indicate the importance of banking management to continuously increase brand awareness and brand loyalty programs and improve perceived quality and brand image in building brand equity to winning the competition among banking companies.